2019
DOI: 10.1371/journal.pone.0214195
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of acupuncture versus standard care for pelvic and low back pain in pregnancy: A randomized controlled trial

Abstract: Objective To assess the cost-effectiveness of acupuncture for pelvic girdle and low back pain (PGLBP) during pregnancy. Design Pragmatic-open-label randomised controlled trial. Setting Five maternity hospitals Population Pregnant women with PGLBP Method 1:1 randomization to standard care or standard care plus acupuncture (5 sessions by an acupuncturist midwife). Main outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 35 publications
1
42
0
2
Order By: Relevance
“…Cost effectiveness of acupuncture as an adjuvant care was also demonstrated in a study examining treatment for women experiencing low back pain associated with pregnancy. 21 In this randomized controlled study, the average total costs in the group receiving standard treatment alone were higher than those for the group receiving standard care plus acupuncture indicating the benefits of adding acupuncture to standard care.…”
Section: Cost Considerationsmentioning
confidence: 71%
“…Cost effectiveness of acupuncture as an adjuvant care was also demonstrated in a study examining treatment for women experiencing low back pain associated with pregnancy. 21 In this randomized controlled study, the average total costs in the group receiving standard treatment alone were higher than those for the group receiving standard care plus acupuncture indicating the benefits of adding acupuncture to standard care.…”
Section: Cost Considerationsmentioning
confidence: 71%
“…The primary time point at which outcomes were measured was a median of 26 weeks postrandomization (Q1/3: 8; 52 weeks; n = 36) ranging from a single day 104 to 5 years. 6 However, there were many studies that assessed outcomes over a period, 5 , 9 , 30 , 34 , 97 , 102 , 106 at flexible time points, 50 , 81 , 108 studies that defined several time points as primary, 75 , 111 and several that did not specify a primary point of follow-up. 3 , 8 , 26 , 59 , 66 , 83 , 109 , 122 A better indicator for how long self-declared pragmatic trials are, may thus be the longest time point of follow-up, for which the median was about one year after randomization (median 50 weeks, Q1/3; 23.25; 52 weeks; n = 56; not reported in one case 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Across our sample of included studies, there was a significant difference in attrition between groups (t(56) = 7.16, P < 0.001) and a third of studies reported differential attrition (19; 33%, n = 57). Where there was differential attrition, it was almost as often into the direction of the control group (9 cases 5 , 16 , 81 , 84 , 97 , 101 , 117 , 127 ) as it was into the direction of the intervention group (11 cases 7 , 9 , 20 , 67 , 81 , 82 , 85 , 87 , 94 , 111 , 118 , 123 ), with intervention groups losing an average of 14.9% (SD 12.9) and control groups losing an average of 14.8% (SD 12.8) of participants until the point of primary follow-up (t(112) = 0.032, P = 0.97), possibly accounting for the fact that both groups were of active interventions in most cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In a systematic review by Andronis et al, 12 acupuncture for chronic LBP was found to be likely cost-effective; however, to our knowledge, no previous trials of acupuncture for ALBP have evaluated the cost-effectiveness of the treatment. One RCT reported by Nicolian et al 14 found acupuncture and usual care to be less costly and more effective than usual care alone in the treatment of pelvic pain and LBP in pregnancy.…”
Section: Introductionmentioning
confidence: 99%